Combination of Side-Swing Flap With Negative-Pressure Wound Therapy Is Superior to Open Excision or Flap Alone in Children With Pilonidal Sinus—But at What Cost? - Dorth, Deborah; Königs, Ingo; Elrod, Julia; Ghadban, Tarik; Reinshagen, Konrad; Boettcher, Michael (Frontiers in Pediatrics, 2021)
BACKGROUND: Pilonidal sinus (PS) disease frequently occurs in adolescents and young adults, and in many cases involves wide excision or local flaps as treatment. These treatments are associated with a significant recurrence rate, a long healing time, and thus absence from school or work. The hybrid technique, which is a combination of side-swing plasty with negative-pressure wound therapy (NPWT) may improve these outcomes. The aim of the study was to compare the latter with other current methods. METHODS: Children presenting with a pilonidal sinus to two referral centers for pediatric surgery from January 2017 till June 2019 and subsequent (1) slide-swing plasty, (2) open excision, or (3) slide-swing plasty in combination with NPWT were included in this retrospective study. Type of therapy, number of interventions, duration of hospitalization, complications, and recurrence rate were recorded. In addition, data was retrieved from the national diagnosis-related group for inpatient statistics, for all patients who underwent surgery for pilonidal sinus in 2015 and 2016. RESULTS: In total, 85 children were included, with a mean age of 15 years and a near equal gender distribution (53% female). The minimum follow-up was one year. In 56% open resection was performed, while 18% underwent a slide-swing plasty and 26% a slide-swing plasty in combination with NPWT. While the hybrid technique was superior regarding recurrence rate in comparison to open excision (24% vs. 5%, p=0.047), it had significantly longer hospital stay (17.41 (15.63) vs. 3.65 (1.68) days, p<0.001) and number of interventions (4.14 (4.07) vs. 1.04 (0.29), p<0.001). CONCLUSIONS: Management of PS disease using slide-swing plasty in combination with NPWT is an effective treatment and is associated with low recurrence rate and minimal morbidity. However, this type of treatment is accompanied by an elongated hospitalization time and more frequent interventions. A diligent case by case evaluation and thorough patient counseling is thus necessary when choosing the right technique for the treatment of PS disease.